2011
DOI: 10.1089/jmf.2010.0265
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Antidiarrheal Studies ofPlinia cauliflora

Abstract: Plinia cauliflora (Mart.) Kausel, widespread in South America, has edible fruits, and its bark is commonly used against diarrhea and other disorders, on account of its astringency. Because diarrhea is still one of the most important causes of illness and death among children in developing countries, where the population turns to traditional medicine for its treatment, the present study determined the composition of fruit and leaf extracts of P. cauliflora, analyzed the activity against diarrhea by antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
0
11
0
2
Order By: Relevance
“…Our results to B. pilosa are in accordance with the results of GARCIA et al (2011) 19 that found the extracts of B. pilosa didn't present significant cytotoxic activity against a human pulmonary tumor cell line A549. SOUZA-MOREIRA et al (2011) 39 evaluated in vitro the cytotoxicity of fruit and leaf extracts of P. cauliflora with the fibroblast cell line SIRC CCL 60, and leaf extract showed a considerable 50% inhibitory concentration of 0.48 µg/mL. In the study of SANTOS PIMENTA et al (2003) 35 , the ethanolic extracts of A. crassiflora leaves did not show cytotoxic activity, but the fractions resulting from solvent extraction showed good brine shrimp larvicidal activity.…”
Section: Resultsmentioning
confidence: 98%
“…Our results to B. pilosa are in accordance with the results of GARCIA et al (2011) 19 that found the extracts of B. pilosa didn't present significant cytotoxic activity against a human pulmonary tumor cell line A549. SOUZA-MOREIRA et al (2011) 39 evaluated in vitro the cytotoxicity of fruit and leaf extracts of P. cauliflora with the fibroblast cell line SIRC CCL 60, and leaf extract showed a considerable 50% inhibitory concentration of 0.48 µg/mL. In the study of SANTOS PIMENTA et al (2003) 35 , the ethanolic extracts of A. crassiflora leaves did not show cytotoxic activity, but the fractions resulting from solvent extraction showed good brine shrimp larvicidal activity.…”
Section: Resultsmentioning
confidence: 98%
“…In vitro studies with peptides purified from P. edulis seeds were active against Trichoderma harzinum , Fusarium oxysporum and Aspergillus fumigatum [ 11 ]. Plinia cauliflora leaf extracts have proven to be effective in management of five different Candida species [ 30 ] and are also active against Enterobacterium fecalis , E. coli , Salmonella and S. sonei [ 24 ]. Anti-microbial activity was also reported in the Psychotria genus with klugin, cephalin, and isocephalin being the chemical compounds responsible for controlling Leishmania donovani and Plasmodium falciparum , and 14-oxoprunifoleine and stricosamide responsible for controlling Leishmania amazonensis.…”
Section: Fruits Species and Their Medicinal Properties: An Updatementioning
confidence: 99%
“…Syzygium cumini fruit juice extract possessed antibacterial and gastroprotective activity [ 28 ]. In order to offer alternative to control childrens’ diarrhoea fruit and leaf extract of Plinia cauliflora was investigated [ 24 ] and it was found that leaf and fruit ethanolic extract was more effective than ampicillin against Enterobacterium fecalis , and leaf extract produced better effects than ampicillin against E. coli and Salmonella sp. but not against S. sonei .…”
Section: Fruits Species and Their Medicinal Properties: An Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Dried jaboticaba peel product is traditionally employed in the treatment of hemoptysis, cough, bronchitis, asthma and inflammation of the tonsils. The fruit peel and leaves are used for diarrhea and dysentery as well, due to their high astringency (Souza-Moreira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%